q-Analogue of Hermite-Hadamard Type Inequalities for s-Convex Functions in the Breckner Sense (Journal of Bhuwanishankar, 2022)
Hermite and Hadamard independently introduced the Herimite-Hadamard inequality for convex functions for the first time. In recent years, a variety of extensions have been made with the use of convex functions by several researchers. In this paper, we have given a variant of the Hermite-Hadamard integral inequality for the s-convex function in the Breckner sense.